2019
DOI: 10.1177/1559325819890498
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Tritium Internal Exposure Doses of Heavy-Water Reactor Workers in Third Qinshan Nuclear Power Plant

Abstract: To analyze the tritium internal exposure dose of workers in the Third Qinshan Nuclear Power Plant over the past 15 years. Urine samples provided by workers are tested directly to analyze the tritium concentrations and estimate internal exposure dose. Since 2004, an average of approximately 1600 workers have been monitored annually, with an average annual monitoring frequency of approximately 11 000. Since 2004, the average annual collective dose of tritium internal exposure was 149.62 person·mSv, accounting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Life span studies on mice demonstrated that the beta particle from tritium is from 1.3–2.0 times as effective as gamma rays in producing chromosome damage (Brooks et al 1976) and increasing cancer risk (Carsten et al 1982). Recent research suggested that low doses of tritium may in fact stimulate the immune system, potentially resulting in a decrease in the risk (Wang et al 2019). With care, tritium in nuclear workers has been limited to levels that are well below established standards and in the range of natural background (Nowosielska et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Life span studies on mice demonstrated that the beta particle from tritium is from 1.3–2.0 times as effective as gamma rays in producing chromosome damage (Brooks et al 1976) and increasing cancer risk (Carsten et al 1982). Recent research suggested that low doses of tritium may in fact stimulate the immune system, potentially resulting in a decrease in the risk (Wang et al 2019). With care, tritium in nuclear workers has been limited to levels that are well below established standards and in the range of natural background (Nowosielska et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Low energy β emitters mainly originate from neutron activation due to their low atomic mass. Radiation protection against internal exposure via intake, inhalation, and ingestion is essential [17,18], while risk arising from external exposure is very slight because of its low energy and short range [19,20].…”
Section: Low Energy Beta-emitter Characteristicsmentioning
confidence: 99%
“…Additionally, neutron capture of 2 H(n, γ) 3 H and 3 He(n, p) 3 H in the reactor evaporator is mainly detected in nuclear facilities. Tritium travels only 6 mm in air, and it cannot penetrate the dead layer of skin [18,24]. It also penetrates only about several micrometers in graphite [25] and less than 1 pm in water [26].…”
Section: Hmentioning
confidence: 99%
“…Recently, also effects induced by low-dose tritium exposure have been investigated in vivo, with a large scale mice study (6)(7)(8)(9) to examine both the biokinetics of tritium and the biological effects of chronic internal exposure, and in vitro in human mammary epithelial cells (10) and in human mesenchymal stem cells (11). Concerning human exposures, epidemiological studies have been conducted on workers, who have been exposed to tritium, but tritiumspecific doses have hardly been the subject of a separate assessment (12). Taken all together, available studies do not provide at present a full assessment of the possible exposure levels and health risks posed by low-dose tritium exposure.…”
Section: Introductionmentioning
confidence: 99%